FRI0291 Clinical Spectrum Time Course in Non Anti Jo-1 Positive Antisynthetase Syndrome. (15th July 2016) - Cavagna, L.; Andersson, H.; González-Gay, M.A.; Molberg, O.; Franceschini, F.; Cavazzana, I.; Castañeda, S.; Lopez Longo, F.J.; Balduzzi, S.; Montecucco, C.; Triantafyllias, K.; Weinmann-Menke, J.; et al.
Abstract : Background: The clinical phenotype of the antisynthetase syndrome (AS) has been related with the underlying autoantibody specificity. The typical disease triad (arthritis, myositis, and interstitial lung disease -ILD) is common in anti Jo-1 + AS, whereas isolated ILD is associated with anti PL-7 and PL-12 Ab. The majority of anti Jo-1 + patients without all triad findings at the onset (incomplete ASSD) will develop lacking features during the followup Objectives: To assess the triad clinical spectrum time course in non anti Jo-1 + AS Methods: The study cohort included patients + for anti-EJ, OJ, PL-7, or PL-12 Ab with at least 1 triad finding. Clinical features were retrospectively collected and analyzed Results: we included 65 non anti Jo-1 + AS (7 anti EJ, 4 anti OJ, 30 anti PL-12, 24 anti PL-7; 49 females, 16 males). In median, age at disease onset was 53 years (IQR 42–64), diagnostic delay 9 months (IQR 3–23.5), followup 60 months (IQR 20.5–113). Patients' characteristics are reported in Table 1 . During the followup, 22/61 patients with incomplete AS developed new triad findings, in median 12 months (IQR 6–27) after disease onset. The frequency of incomplete AS developing new triad findings and the length of followup were significantly reduced in non anti Jo-1 + patients with respect to our corresponding anti Jo-1 + cohort (respectively: 22/61 vs 138/220, p<0.001; median 60 months, IQR 18.5–113 vs median 75 months, IQR 39–134; p=0.002) Conclusions: In non anti Jo-1 + patients the ex novo occurrence of classic triad finding is common, but less frequent than in anti Jo-1 + patients. The different length of followup may explain at least partly this difference References: Cavagna L, et al. Medicine (Baltimore) 2015;94:e1144 Disclosure of Interest: None declared